Prediction of the early part of echograms indispensable in computer simulation in rooms - HOJAN, E.; PÖSSELT, Ch. (Archives of Acoustics, 1991)
The paper discusses the possiblility of an optimal selection of the early part of the room echogram during its calculation in computer simulation. The existence of two such time segments in the echogram has been found. In the first time segment it is necessary to follow precisely successive reflections. In the second time segment the reflections can be treated stochastically.